Ending checkbox diversity : rewriting the story of performative allyship in corporate America - Fountain, Dannie Lynn (Berrett-Koehler Publishers, Inc., 2022)
"American Workplaces have put major resources into increasing diversity and inclusion, yet the outcome has been minimal. Based on her Google experience, Dannie Lynn Fountain shows how companies can move beyond performing to authentically enacting true DEI"--